Relationship between Oil Prices and Exchange Rate of Major Asian Economies: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This Paper studies the relationship between oil prices and exchange rate of three major Asian economies, namely- JAPAN, INDIA and CHINA. Study applies ADF test to check the stationary of time series and the all the series under study stationary at level. Further, Study applies Johansen co integration technique to on time series data ranging from March 2011 to December 2017 to check the short term and long term relationship respectively. Results of Johansen Co integration indicate the significant long term relationship between the oil prices and exchange rate of three major Asian economies.